History Unearthed. A Survey of Eighteen Archaeological Sites throughout the World - Woolley, Leonard (1958)
Nimrud; Ur of the Chaldees; Mohenjo-Daro; the Cities of the Indus Valley; Ras Shamra-Ugarit; Karatepe.